Achievers or Slackers? Per Capita Income Trends in European Countries - Noguera-Santaella, J (Elsevier B.V., 2018)
This paper studies the catching up process of the per capita income of Western European countries for the 1870–2014 period. The contribution to the literature is twofold. First, the use of the Kejriwal and Perron (2010) algorithm allows us to detect any number of structural breaks in the level and in the trend without prior knowledge of the integration order. This is a significant improvement over the algorithms previously used in the literature which limits the number of possible structural breaks to two. In fact, we find that some countries show more than two breaks. Second, we use the longest data series in the literature. That enables us to tell a much richer story about the catching up process in Western Europe. We find that events like the World Wars, the creation of the European Economic Community and the information technology revolution, among others, were likely to cause such breaks. © 2018 The Society for Policy Modeling